Factors associated with success in first-year accounting after the implementation of the National Senior Certificate - Oosthuizen, Annelie; Eiselen, Riëtte (University of the Free State, 2012)
English: Questions have been raised as to whether the National Senior Certificate curriculum, awarded for the first time in 2008, adequately equips learners to achieve academic success at university. This article aims to identify factors associated with success in accounting at university after the implementation of the National Senior Certificate. Differences between students who failed and those who passed Accounting 1 in 2009 are explored in terms of their exposure to, and performance in accounting and mathematics at school level as well as differences in their perceptions of critical skills acquired in the National Senior Certificate. The findings of this study create a platform for continued debate on admission requirements and the importance of specific skills required for success in accounting studies at university.

Afrikaans: Vrae is gestel of die Nasionale Senior Sertifikaat-kurrikulum, wat vir die eerste keer in 2008 toegeken is, leerders voldoende toerus om akademiese sukses op universiteit te behaal. Die doel met hierdie artikel is om faktore geassosieer met sukses in rekeningkunde, ná die implementering van die Nasionale Senior Sertifikaat, te identifiseer. Verskille tussen studente wat Rekeningkunde 1 in 2009 gedruip het en diegene wat dit geslaag het word ondersoek in terme van hul blootstelling aan en prestasie in rekeningkunde en wiskunde op skoolvlak sowel as verskille in hul persepsies omtrent die verwerwing van kritiese vaardighede in die Nasionale Senior Sertifikaat. Die bevindinge van hierdie studie skep ’n platform vir volgehoue debat oor toelatingsvereistes en die belangrikheid van spesifieke vaardighede wat benodig word vir sukses in rekeningkunde-studie aan ’n universiteit.
Keywords: Academic achievement; Accounting; First-year students